Design, synthesis and biological evaluation of novel thiazole-based derivatives as human Pin1 inhibitors. (1st January 2021) - Du, Lifei; Wang, Xiaoyu; Cui, Guonan; Xu, Bailing
Graphical abstract: Abstract: Pin1 is a peptidyl prolyl cis - trans isomerase (PPIase) and inhibiting Pin1 is a potential way for discovering anti-tumor agents. With an aim to find potent Pin1 inhibitors with a novel scaffold, a series of thiazole derivatives with an alicyclic heterocycles on the 2-position were designed, synthesized and tested against human Pin1. Compound 9p bearing a 2-oxa-6-azaspiro [3, 3] heptane moiety on the thiazole scaffold was identified as the most potent Pin1 inhibitor of this series with an IC50 value of 0.95 μM. The structure-activity relationship (SAR) and molecular modeling study indicated that introducing an alicyclic ring with an H-bond acceptor would be a viable way to improve the binding affinity.